Destination, Experience, Social Network, and Institution: Exploring Four Academic Exchange Pull Factor Dimensions at a University in the Republic of Korea - Lee, Kyungsuk; Stewart, Willam H. (Journal of International Students, 2022)
Korean universities have shown a dramatic change in international student enrolment over the last 20 years. While a notable increase in enrolment is undeniable, factors related to international students at Korean universities are not well known or are poorly understood. In this exploratory correlational study, we investigated the relationship between gender and study level using the push–pull model among four pull factor dimensions: (a) Appeal of Korea, (b) Experiential Motivations, (c) Social Network Influences, and (d) Institutional Appeal. Short-term exchange students (N = 601) showed that Experiential Motivations was the most salient pull factor dimension in general. A 2x3 analysis of variance indicated statistically significant differences by gender and study level among the four pull factor dimensions. We conclude by discussing mobility programs and the need to account for the different motivations of potential students typologically in order to design policies and programs more effectively.